C–O cleavage of aromatic oxygenates over ruthenium catalysts. A computational study of reactions at step sites1. Issue 23 (21st June 2015) - Chiu, Cheng-chau; Genest, Alexander; Borgna, Armando; Rösch, Notker
<x xml:space="preserve">Abstract</x> C–O scissions of catecholate and phenolate on stepped Ru surfaces have accessible barriers. Computational results illustrate that benzene formation in the hydrodeoxygenation of aromatics over Ru occurs at step sites.